2016
DOI: 10.1364/oe.24.009794
|View full text |Cite
|
Sign up to set email alerts
|

Multi-gigabit/s underwater optical communication link using orbital angular momentum multiplexing

Abstract: In this work we experimentally demonstrated an underwater wireless optical communications (UWOC) link over a 2.96 m distance with two 445-nm fiber-pigtailed laser diodes employing Orbital Angular Momentum (OAM) to allow for spatial multiplexing. Using an on-off keying, non-return-to-zero (OOK-NRZ) modulation scheme, a data rate of 3 Gbit/s was achieved in water with an attenuation coefficient of 0.4128 m-1 at an average bit error rate (BER) of 2.073 × 10-4, well beneath the forward error … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 196 publications
(54 citation statements)
references
References 21 publications
1
52
0
Order By: Relevance
“…Baghdady et al realized 3Gbit/s UOC system with two OAM modes multiplexing for link distance 2.96m by taking advantage of this characteristics of OAM modes [17]. Similarly, Ren et al achieved a higher transmission rate, 40Gbit/s, for a UOC system by using four OAM multiplexed modes [18].…”
Section: Introductionmentioning
confidence: 99%
“…Baghdady et al realized 3Gbit/s UOC system with two OAM modes multiplexing for link distance 2.96m by taking advantage of this characteristics of OAM modes [17]. Similarly, Ren et al achieved a higher transmission rate, 40Gbit/s, for a UOC system by using four OAM multiplexed modes [18].…”
Section: Introductionmentioning
confidence: 99%
“…Shown in Figure 8 6 are the captured images of beams of charge numbers m=±4 after propagation through a phase plate of charge m=-4. In Figure 8 6 (a) only the m=-4 beam is allowed to propagate across the channel before reaching the m=-4 phase plate and becoming a beam of charge m=-8.…”
Section: Resultsmentioning
confidence: 99%
“…A possible way to increase the transmission capacity of UWOC link is to use multiple OAM modes, as demonstrated in [132]- [136] and reviewed in [137]. Baghdady et al performed experimental demonstration of a 3 Gbit/s underwater communication link, using two 445 nm lasers, and successfully transmitted the signal over a distance of 2.94 m modulated on a simple on-off keying non-return to zero (OOK-NRZ) scheme [134]. In [135], Ren et al reported an aggregated data rate of 40 Gbit/s, using 4 green OAM modes over 1.2 m of turbulent tap water.…”
Section: Underwater Communicationmentioning
confidence: 99%